STRATEGI PENINGKATAN MUTU DALAM PENGGUNAAN TRANSPORTASI DARAT - Kutaibah Al Muharrir; Nabil Shafwan, Topan Adi Saputra, Siti Sahara (CV. ADIBA AISHA AMIRA, 2023)
Land transportation is a vehicle with all kinds of forms that use the road as a route to carry passengers or goods. This research was conducted with the aim to find out what kind of problems can reduce the quality of the use of land transportation and identify strategies that can improve the quality of using land transportation. This research was carried out using a qualitative step with a description of the results and discussion in the form of a descriptive. The data is sourced from reference literature related to the topic. The results obtained are strategies that can be used to improve the quality of land transportation in the form of saving fuel use, reducing the use of private vehicles and switching to public transportation, minimizing the number of accidents vehicle.